Analysis of Merit System on Filling High Leadership Positions in the Government of East Manggarai Regency - Novita Rusdiyani; Eko Prasojo (West Science Interdisciplinary Studies, 2023)
The purpose of this research is to analyze the application of merit system in the implementation of open selection for high leadership positions in the context of a local socio-cultural setting. The merit system policy in this open selection in this research refers to the Regulation of the Minister of Administrative Reform and Bureaucratic Reform (Permenpanrb) Number 15 of 2019. This research was conducted in the East Manggarai Regency Government utilizing a post-positivist research approach with qualitative data collection techniques. The findings showed that the implementation of open selection for filling JPT in East Manggarai Regency was not based on succession planning, there were differences in administrative requirements with relevant regulations; the addition of several administrative files. The background checking process is only carried out based document-driven and conducted indirectly to the participants’ work environment. The process of monitoring and evaluation or re-mapping for elected officials is carried out periodically. The limited number of elected officials with different socio-cultural backgrounds is due to the composition of employees and selection participants who mostly come from the East Manggarai Regency area and share the same socio-cultural background. Keywords: Civil Service, Merit System, Open Selection, Primordialism.